ANALISIS PUTUSAN PENGADILAN NEGERI SAMPANG NOMOR 69/Pid.B/2012/PN.Spg. PRESPEKTIF HAK KEBEBASAN BERAGAMA DI INDONESIA - Muwaffiq Jufri (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2016)
the rights and freedom of religion is a constitutional right of citizens as guaranteed by the constitution. However, conflict, violence and prohibition on the right is still prevalent in various regions in Indonesia, only one is against followers of Syi'ah in Sampang. These events drove Tajul Muluk be convicted by Sampang District Court's Decision No.69/Pid.B/2012/PN.Spg. This event seemed to signal that the state is unable to protect the constitutional rights of citizens to believe in and follow a religion. Even countries participated as an actor against the rise of violence and a rejection of the Syi’ah community in Sampang. The attitude of such state is a form of a waiver of the principle of religious freedom guaranteed by the constitution.